2017
DOI: 10.1371/journal.pntd.0005394
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito cell-derived West Nile virus replicon particles mimic arbovirus inoculum and have reduced spread in mice

Abstract: Half of the human population is at risk of infection by an arthropod-borne virus. Many of these arboviruses, such as West Nile, dengue, and Zika viruses, infect humans by way of a bite from an infected mosquito. This infectious inoculum is insect cell-derived giving the virus particles distinct qualities not present in secondary infectious virus particles produced by infected vertebrate host cells. The insect cell-derived particles differ in the glycosylation of virus structural proteins and the lipid content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This is the first description of how ZIKV RNA levels correspond to infectious virus particles. The ZIKV ratio is similar to reported ratios for the flaviviruses DENV and yellow fever virus, which have GE:PFU ratios of 1-5x10 3 [ 52 , 53 ], but is approximately 10-fold higher than WNV [ 54 56 ]. The GE:PFU ratio of ZIKV mam was 2–7 fold higher than ZIKV mos , similar to the difference observed between mammalian cell- and mosquito cell-produced WNV [ 55 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is the first description of how ZIKV RNA levels correspond to infectious virus particles. The ZIKV ratio is similar to reported ratios for the flaviviruses DENV and yellow fever virus, which have GE:PFU ratios of 1-5x10 3 [ 52 , 53 ], but is approximately 10-fold higher than WNV [ 54 56 ]. The GE:PFU ratio of ZIKV mam was 2–7 fold higher than ZIKV mos , similar to the difference observed between mammalian cell- and mosquito cell-produced WNV [ 55 ].…”
Section: Discussionsupporting
confidence: 81%
“…C6/36 cells do not demonstrate CPE, and may produce virus longer than Vero cells, which succumb to infection. Similarly, C6/36 cells demonstrate sustained production of subgenomic replicon particles for up to 10 days after transfection [ 54 ]. The disparity in maintaining high levels of virus may reflect host physiological differences with important implications on flavivirus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection methods using regular lipid-based transfection reagent are supposed to have mainly been optimized to be used on mammalian cell lines that are cultured at 37 °C. Accordingly, when applying the same transfection protocol to other vertebrates or invertebrate cells like fish or mosquito cells, which are cultured at lower temperature (5–15 °C), the efficiency of transfection decreases and is often below 10% 14 , 25 . While a low percentage of transfection may be sufficient for some studies, the rescue of recombinant viruses from overlapped DNA amplicons often requires higher transfection efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the ISA method could be adapted to Aedes mosquito cells remained to be demonstrated. Second, previous studies using electroporation and/or transfection with regular lipids-based reagents of RNA in Aedes mosquito cells demonstrated a very low efficiency of RNA delivery (ranging from 0.2 to 10%) 14 , 15 . Therefore, new powerful method of nucleic acids delivery in Aedes mosquito cells is needed and especially to be applied to the ISA reverse genetics system.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of particles per infectious unit in the initial viral stocks ranged from 8 to 600 [ 98 ]. Our viral stocks had a similar ratio of particles per infectious unit as that seen produced by fully infectious extracellular WN virus particles [ 100 ] and mosquito-derived replicon WN virus particles [ 101 ]. Variances in replication efficiency between studies observed during in vitro infection could be explained to differences in the viral strain and to the infection conditions i .…”
Section: Methodsmentioning
confidence: 99%